PENGARUH SANITASI LINGKUNGAN DAN AKSES AIR BERSIH TERHADAP STUNTING PADA SISWA SEKOLAH DASAR - Nida Nabilah Limas; Anna Maria Oktaviani; Sulistiawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Stunting is a chronic nutritional problem that remains prevalent among elementary school children and can have long-term impacts on health, learning capacity, and overall human resource quality. Environmental factors, particularly sanitation conditions and access to clean water, play a crucial role in supporting optimal child growth and development. This study aimed to analyze the influence of environmental sanitation and access to clean water on the occurrence of stunting among elementary school students. A quantitative approach with a cross-sectional design was employed in this study. The research participants consisted of 60 elementary school students from SDN Citerep. Stunting status was determined through anthropometric measurements based on height-for-age standards, while data on environmental sanitation and access to clean water were collected using structured questionnaires completed by parents or guardians. Data analysis was conducted using descriptive and analytical methods through cross-tabulation to examine the distribution and associations between variables. The results showed that the prevalence of stunting among elementary school students was 30.0%. Stunting was more frequently observed among students living in environments with poor sanitation, where 14 out of 30 students were classified as stunted, compared to those with good sanitation conditions. In addition, a higher proportion of stunting cases was found among students with inadequate access to clean water, with 13 out of 25 students experiencing stunting, compared to students who had adequate access to clean water. These findings indicate that environmental sanitation and access to clean water are influential factors associated with the occurrence of stunting among elementary school students. Therefore, stunting prevention efforts should adopt an integrated approach that not only focuses on improving nutritional intake but also emphasizes the improvement of environmental sanitation and the expansion of adequate clean water access in both household and school settings.